Episodic and chronic migraine - treatment and risk factors - A literature review - Skrzypek, Jakub; Jagoda Niewiadomska; Borys Bondos; Aleksandra Stępień; Alicja Paluch; Aleksandra Niekra; Łukasz Fussek; Robert Kochan; Ewelina Wieczorek; Kacper Lee (Journal of Education, Health and Sport, 2024)
Abstract Introduction and objective Migraine is a chronic paroxysmal neurological disease characterised by attacks of moderate to severe headache and accompanying symptoms such as hypersensitivity to light and sound and gastrointestinal disturbances such as nausea and vomiting, among others. In some people, an attack of pain is preceded by a migraine aura - visual disturbances, numbness, tingling and even muscle weakness. Treatment includes medications taken as a temporary measure (at the onset of an attack) and as a prophylactic measure. The aim of this study is to systemasise information about chronic migraine and to raise awareness about this disease among health care workers and patients Brief description of the state of knowledge Migraine is a recurrent, usually unilateral, throbbing headache. A migraine usually lasts between 4 and 72 hours. It is characterised by varying degrees of severity and frequency of occurrence. The pain is exacerbated by emotion or physical exertion. There is photophobia, hypersensitivity to sounds (phonophobia) and odours (osmophobia), and nausea and vomiting occur. Sometimes before a migraine episode occurs, a so-called aura - occurring in 10% of migraine cases may appear, in the form of paresthesias, visual field loss, appearance of gloom, paresis, aphasia. Chronic migraine is a headache that occurs for at least 15 days per month, at least 8 of which are days when the headache has the characteristics of migraine pain as described below or is relieved by prescription anti-migraine medication. There are many triggers for migraine, which include genetic, environmental and personal factors. Chronic migraine severely reduces the quality of life of affected patients, therefore it is important to raise awareness of currently available methods for its diagnosis and treatment